Development of a robust method to derive human trophoblast stem cells from late-gestation placentas and its application to preeclampsia - Akira Oike; Eri H. Kobayashi; Yasuhiro Yamamoto; Hirotaka Hamada; Sota Takahashi; Takanori Shimizu; Akane Kitamura; Asato Sekiya; Norio Kobayashi; Shun Shibata; Shun Endo; Tetsuya Sato; et al. (Proceedings of the National Academy of Sciences, 2026)
Trophoblasts are multifunctional cells in the placenta and essential for normal pregnancy. Although trophoblast dysfunction can cause pregnancy complications, the underlying mechanisms remain unclear, and effective treatments are limited, partly because of the scarcity of appropriate experimental models. We previously reported the derivation of human trophoblast stem cells (hTSCs) from 1st-trimester placentas and blastocysts, providing a powerful tool to investigate human trophoblast development and function. However, the difficulty in deriving hTSCs from late-gestation placentas has limited their application to pregnancy complication research. Here we report a robust technique to derive hTSCs from term placentas based on the transient expression of a p53 dominant negative mutant, SALL4, and shRNAs against cyclin-dependent kinase inhibitors. Using this technique, we derived and characterized hTSCs from placentas obtained from patients with early-onset preeclampsia (PE). PE-derived hTSCs exhibit impaired trophoblast invasion and reduced placental growth factor secretion, consistent with trophoblast abnormalities reported in PE. Therefore, this study provides a technological basis for investigating pregnancy complications associated with trophoblast dysfunction.